2011
DOI: 10.1097/coc.0b013e3181e9c103
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Gemcitabine in Combination With Radiation Therapy in Patients With Localized, Unresectable, Pancreatic Cancer

Abstract: The activity and toxicity profile of combination GEM and RT indicates that this can be safely administered for patients with LAPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 19 publications
3
25
0
1
Order By: Relevance
“…This compares favorably with the outcome reported with exclusive chemotherapy or radiochemotherapy [18,19] for the same category of patients. Our study confirms that it remains difficult to assess the response to preoperative treatment with conventional radiological or biological techniques and that the lack of progression after neoadjuvant systemic therapy currently remains the only selection criterion for surgery in pancreatic cancer patients with such LA disease.…”
Section: Discussionsupporting
confidence: 73%
“…This compares favorably with the outcome reported with exclusive chemotherapy or radiochemotherapy [18,19] for the same category of patients. Our study confirms that it remains difficult to assess the response to preoperative treatment with conventional radiological or biological techniques and that the lack of progression after neoadjuvant systemic therapy currently remains the only selection criterion for surgery in pancreatic cancer patients with such LA disease.…”
Section: Discussionsupporting
confidence: 73%
“…Patients receiving chemotherapy in addition to chemoradiation had a median survival of 18.7 versus 12.4 months (p = 0.02) for patients receiving chemoradiation alone. Other studies, although underpowered, suggested that the addition of chemoradiation to gemcitabine therapy conferred a marginal survival benefit with comparable toxicity profiles [33,34]. Correspondingly, CRT usually follows induction chemotherapy which allows for identification of patients, approximately 30%, with initially undetected metastatic disease [35,36].…”
Section: Neoadjuvant Chemoradiationmentioning
confidence: 99%
“…It does appear that resectability rates are higher following FOLFIRINOX then they are after non-FOLFIRINOX regimens [6][7][8][9][10][11][12][13] , in which the resectability rates for locally unresectable (stage III) patients treated with induction therapy have ranged between 7%-19%. Small et al 9 reported a multi-institutional phase II study, which assessed the efficacy of gemcitabine with concurrent radiation therapy in nonmetastatic PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the pre-FOLFIRINOX era, the conversion rates of stage III patients with induction therapy ranged between 7-19% [6][7][8][9][10][11][12][13] . Currently, the resectability rates after induction FOLFIRINOX for stage III PDAC are not established, as recent series assessing FOLFIRINOX for non-metastatic patients have been either single-arm surgical series with a denominator limited to selected patients who were taken to the operating room, or series composed of a heterogonous population that included both resectable and locally unresectable patients 14 .…”
Section: Introductionmentioning
confidence: 99%